Estudo sobre assessorias de comunicação social na esfera pública estadual: práticas profissionais e processo comunicacional - Wels, Ana Maria Córdova (Organicom, 2006)
The first consulting agencies in the field of social communication to public agencies in the executive sector of the state of Rio Grande do Sul emerged in the 70’s, following a model already adopted in the federal level, with the constitution of the Special Agency of Public Relations. For the higher dialogue with the society, these consulting agencies had, as one of its main tasks, the mediation between the government and the media, to provide information about government actions and its subsequent public image spread.